A Study on Brand Preferences of Washing Soaps in Rural Areas - Anandan, C.; Prasanna Mohan Raj, M.; Madhu, S. (Indian Journal of Marketing, 2006)
India’s rural markets have seen a lot of activity in the last few years. Since penetration levels are pretty high in most categories, future growth can come only from deeper rural penetration. Rural marketing has become the latest marketing mantra of most FMCG majors. True, rural India is vast with unlimited opportunities, waiting to be tapped by FMCG majors. To gain advantage of this, the Indian FMCG sector is busy putting in place a parallel rural marketing strategy. FMCG majors are aggressively looking at rural India since it accounts for 70% of the total Indian households.Today, India has a diverse range of detergents available off the shelf. The annual consumption of detergents in India ranges to thousands of tonnes. The formal sector with its increasing ability to influence consumers via advertisements is expanding its market share aggressively. The detergent market has evolved into a highly competitive one where myriad brands vie with each other to get the customers’ attention. Each brand claims to clean whiter, boasting of technologically dubious terms such as fighting granules, power pearls, etc. This study aims at finding the factors influencing the rural customers to prefer a particular brand in detergent soaps. This study concludes with suggesting the strategic framework for Marketers to win over the hearts of the rural customers.